ANALISIS PREFERENSI PELAKU UMKM DALAM MEMILIH BANK DENGAN PENERAPAN TEORI PERMAINAN - NAKISOMA, IRENE; TASTRAWATI, NI KETUT TARI; SARI, KARTIKA (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
Business actors require banking services that effectively support their financial activities. The variety of available banks requires institutions to understand customer preferences in order to develop competitive strategies. This study aims to determine the optimal strategy that banks may implement based on the preferences of micro, small, and medium business actors using game theory. The research employed a two-stage data collection process. The first stage involved 30 respondents to identify the two most preferred banks, namely Bank A and Bank B. The second stage involved 108 respondents, determined through the Yamane formula, to evaluate eight strategic banking attributes. Payoff values were calculated using the difference in preference probabilities for each attribute. Game theory analysis used a two-person zero-sum game with pure strategies. The results indicate that Bank A optimal strategy is ATM availability, while Bank B optimal strategy is loan interest rates. These findings may assist banks in enhancing their services according to business actors’ preferences.